Efficacy of Gamithromycin for the Treatment of Foals with Mild to Moderate Bronchopneumonia. (January 2015) - Hildebrand, F.; Venner, M.; Giguère, S.
<x xml:space="preserve">Abstract</x> Background Gamithromycin is active in vitro against the bacterial agents most commonly associated with bronchopneumonia in older foals. However, the clinical efficacy and safety of this drug have not been investigated. Hypothesis Gamithromycin is effective for the treatment of bronchopneumonia in foals. Animals One hundred and twenty‐one foals on a farm endemic for infections caused by Rhodococcus equi. Methods In a controlled, randomized, and double blinded clinical trial, foals with ultrasonographic evidence of pulmonary abscesses (abscess score 8.0–20 cm) were randomly allocated in 3 treatment groups: (1) gamithromycin IM q7 days (n = 40); (2) azithromycin with rifampin, PO q24h (n = 40); or (3) no antimicrobial treatment (controls; n = 41). Physical examination and thoracic ultrasonography were performed by individuals unaware of treatment group assignment. Foals that worsened were removed from the study. Results The proportion of foals that recovered without the need to be removed from the study was significantly higher for foals treated with gamithromycin (38 of 40) or azithromycin with rifampin (39 of 40) than for controls (32 of 41). Treatment with gamithromycin or with azithromycin‐rifampin resulted in a significantly faster decrease in the clinical score and abscess score compared to the controls. Adverse reactions characterized by colic (n = 18) and hind limb lameness (n = 14) were observed only in foals treated with gamithromycin. Conclusion and Clinical Importance Gamithromycin was noninferior to azithromycin with rifampin for the treatment of bronchopneumonia in the study population but had a higher frequency of adverse reactions.